2013
DOI: 10.1530/rep-12-0081
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modelling in developmental biology

Abstract: In recent decades, molecular and cellular biology has benefited from numerous fascinating developments in experimental technique, generating an overwhelming amount of data on various biological objects and processes. This, in turn, has led biologists to look for appropriate tools to facilitate systematic analysis of data. Thus, the need for mathematical techniques, which can be used to aid the classification and understanding of this ever-growing body of experimental data, is more profound now than ever before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…We focus on the features to which biologists may wish to pay attention to appreciate the main modelling assumptions and the type of information that can be gained from a specific computational study. More mathematically oriented reviews in relation with the modelling techniques described here below can be found in (Newman, 2005;Soneji et al, 2007;Zhou and Huang, 20011;Swat et al, 2012;Vasieva et al, 2013;D'Alessandro et al, 2014), among others. In this section, when listing various modelling approaches, we mainly refer to models that will be discussed later in this review.…”
Section: Key Modelling Choicesmentioning
confidence: 99%
“…We focus on the features to which biologists may wish to pay attention to appreciate the main modelling assumptions and the type of information that can be gained from a specific computational study. More mathematically oriented reviews in relation with the modelling techniques described here below can be found in (Newman, 2005;Soneji et al, 2007;Zhou and Huang, 20011;Swat et al, 2012;Vasieva et al, 2013;D'Alessandro et al, 2014), among others. In this section, when listing various modelling approaches, we mainly refer to models that will be discussed later in this review.…”
Section: Key Modelling Choicesmentioning
confidence: 99%
“…Mathematical modeling is an excellent method that has been used successfully to study many developmental processes (Fletcher et al, 2017;George et al, 2015;George and Lubkin, 2018;Vasieva et al, 2013). It has significantly improved our understanding of zebrafish development (Sharpe, 2017;Wertheim and Roose, 2017;Yamaguchi et al, 2007;Zhu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Biological pattern formation is a complex phenomenon which is studied experimentally in a number of model organisms [1] and theoretically by means of various mathematical techniques [2,3]. One of the model organisms commonly used in biological studies of pattern formation is the fly (Drosophila) embryo [4].…”
Section: Introductionmentioning
confidence: 99%